Cytokine Responses to Acute Exercise in Healthy Older Adults: The Effect of Cardiorespiratory Fitness - Windsor, Mark T.; Bailey, Tom G.; Perissiou, Maria; Meital, Lara; Golledge, Jonathan; Russell, Fraser D.; Askew, Christopher D. (Frontiers in Physiology, 2018)
Markers of chronic inflammation increase with ageing, and are associated with cardiovascular disease prevalence and mortality. Increases in fitness with exercise training have been associated with lower circulating concentrations of cytokines known to have pro-inflammatory actions (such as interleukin-6 [IL-6]) and higher circulating concentrations of anti-inflammatory cytokines (interleukin-10 [IL-10]). However, the effect of cardiorespiratory fitness on acute cytokine responses to a single bout of exercise in healthy older individuals is unknown. We compared the response of plasma cytokines IL-6, tumour necrosis factor-alpha (TNF-α) and IL-10 to a bout of moderate-intensity continuous and higher-intensity interval exercise between older individuals with higher and lower levels of cardiorespiratory fitness. Sixteen lower-fit (V̇O2peak: 22.6±2.8 mL.kg-1.min-1) and fourteen higher-fit participants (V̇O2peak: 37.4±5.9 mL.kg-1.min-1) completed three 24 min experimental protocols in a randomised order: 1) moderate-intensity continuous exercise (40% of peak power output [PPO]); 2) higher-intensity interval exercise (12 x 1 min intervals at 70% PPO separated by 1 min periods at 10% PPO); or 3) non-exercise control. Plasma cytokines were measured at rest, immediately after, and during 90 min of recovery following exercise or control. Plasma IL-6 concentrations at baseline were greater in the higher-fit compared to the lower-fit group (P=0.02), with no difference in plasma IL-10 or TNF-α concentrations at baseline between groups. Plasma IL-6 and IL-10 concentrations in both groups increased immediately after all protocols (IL-6: P=0.02, IL-10: P<0.01). However, there was no difference in the IL-6 and IL-10 response between the exercise and non-exercise (control) protocols. After all protocols, no changes in plasma TNF-α concentrations were observed in either the higher- or lower-fit groups. In this study, basal concentrations of circulating IL-6 were elevated in older individuals with higher levels of cardiorespiratory fitness. However, changes in plasma cytokine concentrations after exercise were not different to changes after non-exercise control in both the lower- and higher-fit groups.